1967
DOI: 10.1007/bf02908367
|View full text |Cite
|
Sign up to set email alerts
|

Observations on response factors for thermal conductivity detectors in GLC analysis of fatty acid methyl esters

Abstract: Various erratum factors have been proposed for quantitative analysis of fatty acid methyl ester mixtures by isothermal gas‐liquid chromatography (GLC) employing thermal conductivity detectors in an effort to obtain more accurate values. These factors include multiplication of the area of each peak by the square root of the molecular weight of each component before calculating the percentage of each compound in the mixture or applying erratums for relative molar response for saturated esters and relative mass r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1968
1968
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…For the estimation of the liquid thermal conductivity of biodiesel fuels, the Robbins Kingrea method, which is a function of the critical temperature, liquid heat capacity, liquid density, and latent heat of vaporization at the normal boiling point, was utilized by Mohamed Ismail et al Separately, Baroncini’s method was used in the work reported by Golovitchev and Yang . Meanwhile, Ra et al used similar experimental methods and group contributions methods to estimate the liquid thermal conductivity of soybean biodiesel. The DIPPR software has also been used successfully for this purpose …”
Section: Biodiesel Thermophysical Properties Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the estimation of the liquid thermal conductivity of biodiesel fuels, the Robbins Kingrea method, which is a function of the critical temperature, liquid heat capacity, liquid density, and latent heat of vaporization at the normal boiling point, was utilized by Mohamed Ismail et al Separately, Baroncini’s method was used in the work reported by Golovitchev and Yang . Meanwhile, Ra et al used similar experimental methods and group contributions methods to estimate the liquid thermal conductivity of soybean biodiesel. The DIPPR software has also been used successfully for this purpose …”
Section: Biodiesel Thermophysical Properties Modelsmentioning
confidence: 99%
“…Thus, this method was used to predict the vapor heat capacity required for the subsequent calculations of vapor viscosity and vapor thermal conductivity . Many different approaches were also used by Ra et al and Chakravarthy et al in order to ensure accurate estimation of the vapor heat capacity of soybean biodiesel.…”
Section: Biodiesel Thermophysical Properties Modelsmentioning
confidence: 99%
“…In calibration studies of gas chromatographic systems for the quantitative analysis of fatty acid methyl esters, Sheppard, Meeks, and Elliott (110) concluded that individual fatty acids require correction factors for both weight and molar determinations. From observations made on response factors for thermal conductivity detectors, Herb, Magidman, and Riemenschneider (53) concluded that the various proposed correction factors for fatty acid methyl VOL. 41, NO.…”
Section: Oils and Fatty Acidsmentioning
confidence: 99%
“…Dietz (182) measured the response factors of a variety of compounds for both the flame ionization detector and the thermal conductivity detector. Other workers (248) suggest that measurement of response factors for a thermal conductivity detector should be performed during temperature programming of the column to reduce differences in response factors observed under different isothermal conditions. Relative molar response factors for C8 to C24 fatty acid methyl esters were reported using the flame ionization detector (649) and for Ci to Ce amines, cyclic amines, and hydrocarbons using a thermal conductivity detector (616).…”
Section: Detectorsmentioning
confidence: 99%